Empowerment, Mobile Technology, and Managerial Support: A Multidimensional Analysis of Work-Life Balance Among Women Engineers - Nor Sham, Nur Izzaty Shahirah Binti; Salleh, Rohani; Saleem, Muhammad Shoaib; Sheikh, Sharifah Syahirah Syed (International Review of Management and Marketing, 2026)
Women’s empowerment is a crucial objective in advocating for women’s rights. Giving women in the energy industry more authority could help them manage work and family obligations. According to studies, mobile technology may have conflicting effects on users’ work-life balance. Organizational intervention, such as managerial support, is crucial to ensuring that employee empowerment and mobile technology usage may improve work-life balance. Thus, it is believed that managerial support could fortify the empowerment initiative and guarantee that mobile technology would improve workers’ work-life balance. Therefore, the purpose of this paper is to investigate how work-life balance is affected by managerial support, mobile technology usage, and women’s empowerment. The originality stems from a thorough examination of how various variables, such as work-life balance, managerial support, mobile technology usage, and women’s empowerment, intersect and influence the lives of female engineers. This study provides significant insights into possibilities for closing the gender gap in engineering while empowering and supporting women in the workplace. This paper discusses the grounded theories, methodology, data analysis results, discussion of findings, and theoretical and practical contributions.